Preparation and properties of an aromatic polyamide fibre derived from a bio-based furan acid chloride. (November 2021) - Cao, Kaikai; Liu, Yufeng; Yuan, Feng; Yang, You; Wang, Jin; Song, Zhicheng; Li, Zhongliang; Wu, Wei; Jiang, Mengjin; Yang, Jun
A high-molecular-weight aromatic polyamide resin incorporating furan-rings (f-resin) was prepared by low-temperature solution polycondensation of bio-based 2, 5-furandiformyl chloride and 3, 4′-diaminodiphenyl ether, in N, N-dimethylacetamide. Further, an aromatic polyamide fibre containing furan-rings (f-fibre) was obtained from the fresin by dry-jet wet spinning, and its structure and properties were investigated. The prepared f-resin showed good solubility and possessed good spinnability in solution. The mechanical, heat-resistance, and flame-retardant properties of the f-fibre were found to be excellent – comparable to or exceeding those of meta-aramid fibre (m-fibre). In addition, the furan acid chloride monomer is bio-based and is derived from abundant resources, unlike petroleum-based monomers. Therefore, f-fibre has good potential and broad application prospects as an environment-friendly and sustainable high-performance material.